Penerapan Konseling Islam Untuk Mengatasi Gangguan Kesehatan Mental Pada Lansia - Annisaa Rahmania Qurrota A'yun (Scidacplus, 2023)
In old age, getting mentally healthy is not easy, declining health status and physical abilities will cause the elderly to slowly withdraw from relationships with the surrounding community. This research is entitled